2016
DOI: 10.1007/s10461-016-1429-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Interactive Toxicity Beliefs and ART Non-adherence Among HIV-Infected Current Drinkers in Mbarara, Uganda

Abstract: Interactive toxicity beliefs regarding mixing alcohol and antiretroviral therapy (ART) may influence ART adherence. HIV-infected patients in Uganda completed quarterly visits for one year, or one visit at 6 months, depending on study randomization. Past month ART non-adherence was less than daily or <100% on a visual analog scale. Participants were asked if people who take alcohol should stop taking their medications (belief) and whether they occasionally stopped taking their medications in anticipation of dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…This finding contributes to the debate regarding whether alcohol has an influence on HIV treatment. Previous studies have discussed possible mechanisms of how alcohol use could negatively affect HIV treatment adherence [9, 31]. One of the hypotheses was that PLH may choose to skip their ART regimens after drinking alcohol for fear of an alcohol-ART interactive toxicity [31, 32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding contributes to the debate regarding whether alcohol has an influence on HIV treatment. Previous studies have discussed possible mechanisms of how alcohol use could negatively affect HIV treatment adherence [9, 31]. One of the hypotheses was that PLH may choose to skip their ART regimens after drinking alcohol for fear of an alcohol-ART interactive toxicity [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed possible mechanisms of how alcohol use could negatively affect HIV treatment adherence [9, 31]. One of the hypotheses was that PLH may choose to skip their ART regimens after drinking alcohol for fear of an alcohol-ART interactive toxicity [31, 32]. Another proposed explanation was that problematic alcohol use often co-occurs with psychiatric disorders that can subsequently impair the ability of PLH to take their daily medications [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both instruments comprise four-point Likert scales with the responses based on occurrence of symptoms during the last week. In each scale, the sum of all items will be calculated and categorized into different levels of mental health disorder: normal (0-4), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), and moderate to severe (≥15) [50,51].…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…However, the long-term success of such efforts to scale-up coverage of ART for PLWHA may be negatively affected by deficits in adherence to the spectrum of HIV care. ART requires adequate adherence (usually defined as intake of at least 95% of ART doses [7,8]) to yield satisfactory clinical outcomes, e.g., suppressing HIV viral replication [9], improving quality of life [10], and preventing transmission [11]. However, a recent meta-analysis indicated that only 77.6% (95% confidence interval [CI]: 71.6-83.1) of Chinese PLWHA on ART maintained adequate adherence [12].…”
Section: Introductionmentioning
confidence: 99%